2019
DOI: 10.1002/hbm.24485
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of glutamatergic and GABAergic neurotransmission in the central mechanisms of theta‐burst stimulation

Abstract: Theta‐burst stimulation (TBS) is a varied form of repetitive transcranial magnetic stimulation (rTMS) and has more rapid and powerful effects than rTMS. Experiments on the human motor cortex have demonstrated that intermittent TBS has facilitatory effects, whereas continuous TBS has inhibitory effects. Huang's simplified model provides a solid basis for elucidating such after‐effects. However, evidence increasingly indicates that not all after‐effects of TBS are as expected, and high variability among individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 65 publications
2
47
0
Order By: Relevance
“…Importantly, growing consensus suggests the role of inhibitory circuits in regulating human motor cortical plasticity . Therefore, in RTT, defects in cortical inhibitory connectivity might also explain alteration in motor plasticity.…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, growing consensus suggests the role of inhibitory circuits in regulating human motor cortical plasticity . Therefore, in RTT, defects in cortical inhibitory connectivity might also explain alteration in motor plasticity.…”
Section: Discussionmentioning
confidence: 98%
“…However, the varying responses to TBS could be related to the difference in the motor function role between hands (mainly fine motor control) and legs (mainly cyclic movement, such as a gait). The different responsibilities in the brain may affect the responsiveness of synaptic plasticity induced by TBS (Li et al, 2019). A study reported that TBS induces significant cortical plasticity in hand muscles, whereas no significant response was observed in arm muscles (Martin et al, 2006).…”
Section: Interindividual Variability In Corticospinal Excitability Chmentioning
confidence: 99%
“…The original TBS article suggests that TBS modulates synaptic plasticity in the circuits under the TMS coil, involving corticospinal excitability for MEPs, inhibitory circuits for SICI, and facilitatory circuits for ICF simultaneously (Huang et al, 2005). Review articles further suggest that both GABAergic and glutamatergic neurotransmission play a crucial in the induction of plasticity by TBS (Suppa et al, 2016;Huang et al, 2017;Li et al, 2019). It is also well-known that SICI is mediated by GABAergic interneurons and ICF could be mediated by glutamatergic interneurons (Ziemann et al, 2015).…”
Section: Relationship Between the Effects Of Tbs And Neurophysiologicmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, conventional rTMS generally takes more than 15 minutes. That the mechanisms of TBS are also dependent on glutamatergic function 4 has been evidenced by the finding that memantine, which is a NMDA receptor antagonist, blocks the aftereffects of cTBS as well as iTBS.…”
Section: Basic Technology and The Neural Mechanisms Underlying Nibsmentioning
confidence: 99%